Aplikasi Customer Relathionship Management Untuk Klasifikasi Pelanggan Menggunakan Algoritma C4.5 - Ruli Utami; Ferry Andhika Primadana; Suryo Atmojo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The Tutoring Institute (LBB) is a business service that is growing in Indonesia, the number of existing competitors greatly affects to customers number who use these tutoring services, so great strategies are needed to attract new customers or retain old customers. To select customers that eligible for the promo package provided by LBB, an application is needed that can accommodate the classification needs of which customers are eligible or not to get the promo. To overcome this problem, it is proposed to build a customer relationship management application with the implementation of the C4.5 algorithm which has a classification function in data mining method. Based on the analysis, data processing, and testing that has been done; it is concluded that the implementation of the C4.5 algorithm is suitable for use in case studies taken with an average accuracy value of 86%. In addition, it is also concluded that the more data used in the training process affects the level of system accuracy, this is evidenced by two tests using different amounts of training data.